The Context of a Business Organization. Theoretical Frameworks - Stańczyk-Hugiet, Ewa (Studia Oeconomica Posnaniensia, 2017)
The article analyses selected theoretical frameworks for explaining the relationships between organizations and their surroundings with an attempt to indicate their importance in the current operating environment of business organizations. The paper is of a theoretical nature and has been based on an in-depth analysis of the cur-rent literature. The analysis of aspects of organizational adaptability and perspectives of population ecology, adaptation perspectives, and entrepreneurial perspectives, as well as the analysis of the determinants of contemporary competitive advantage with special attention to disruptions and emergence leads to the conclusion that problems of disruption, emergence, volatility, paradigm of imbalance, dynamic models and adaptation are the main contextual dimensions. Therefore, it is impossible to solve the adaptation problem from a single actor analysis.